Assistance Program for the Utilization of Local Assets in the Development of Natural Colored Batik by the Community of the Kebon Gedang Block, Ciwaringin Village, Ciwaringin District Cirebon Regency - Amir Macmud; Bustaman (PT FORMOSA CENDEKIA GLOBAL, 2022)
This asset-based approach has the goal of focusing on identifying and utilizing existing assets rather than focusing on deficiencies or problems. The activity of utilizing local assets carried out by the people of Kampung Gedang aims to make the life of the local community better and independent by utilizing the existing potential, starting from the use of natural materials, human resources, to local facilities and infrastructure to support the development of written batik. The method used in this activity is a descriptive research method with a qualitative approach, using literature studies and other secondary data from various sources. The discussion shows that the ABCD stage is a step that can be taken to support the development of Ciwaringin Batik, by adopting this concept, community development steps through batik can be carried out properly.